A Comparison of Ultrasound and MRI Measurements of the Cross-Sectional Area of the Median Nerve at the Wrist. (November 2019) - Hersh, Beverly; D'Auria, Jennifer; Scott, Michael; Fowler, John R.
Background: Ultrasound (US) measurement of cross-sectional area (CSA) of the median nerve has emerged as a viable alternative to electromyography/nerve conduction studies (EMG/NCS) for diagnosis of carpal tunnel syndrome (CTS). The purpose of this study is to compare CSA of the median nerve between US and MRI using current MRI and US technology. The null hypothesis is there is no difference between US and MRI CSA measurements.Methods : The study design was an observational cohort, enrolling patients presenting to clinic with MRI of the wrist. Participants with clinical signs and symptoms of CTS were excluded. The CSA measurements of the median nerve on MRI T1-weighted axial images were performed by a hand fellow blinded to results of US measurements, and US measurement of median nerve CSA was performed by a hand fellowship trained surgeon blinded to results of the MRI measurements. Results were analyzed via percent error, Pearson correlation, and t tests.Results: Twenty participants were enrolled with mean age of 29.4 years. Four left wrists and 16 right wrists were measured. The US mean CSA of the median nerve was 6.8 mm 2 (±2.330 mm 2 ). The MRI mean CSA of the median nerve was 6.8 mm 2 (±2.153 mm 2 ), P = .442. Pearson correlation between modalities was 0.93, suggesting near-perfect correlation. Mean percent error was 8.8%.Conclusions : Results of this study suggest that US is an accurate method to measure CSA of the median nerve at the carpal tunnel inlet. The mean difference between US and MRI was unlikely to be clinically significant.